Isolated Adult Congenital Anterior Urethrocutaneous Fistula: A Rare Anomaly and Review of Literature - Al Demour, Saddam; Alrabadi, Adel; Abubaker, Ahmad; Aljamal, Sa’id (Jordan Medical Journal, 2018)
Congenital anterior urethrocutaneous fistula of the male urethra is a rare deformity, frequently locatedat the subcoronal level. It is usually accompanied by anorectal and genitourinary malformations, butmay present as a very rare, isolated anomaly along with a normal urethra and meatus. The adult type ofisolated congenital anterior urethrocutaneous fistula is an extremely rare anomaly, with only two suchcases previously reported in the English language literature. This case report presents an adult patientwith this rare deformity.